From Greed to Justice - Mona Abul-Fadl (American Journal of Islam and Society, 1992)
I would like to seize the opportunity of the theme of this conference to highlight some of the flaws which taint and constrain American foreign policy in the Middle East and, more generally, in the Muslim world. I do so with the purpose of exploring the possibilities for a change which would be to the advantage of all parties concerned, for while I believe that America’s Middle East policy is largely prompted by considerations of national self-interest and expediency, and that these might be subsumed under the category of ‘‘greed,’’ there still remains a recurrent undertone and preoccupation with a moral self-justification that seeks grounds of justice and right for all its pursuits. Beyond greed and morality, however, the determining factor for both dimensions is contingent upon our perceptions, conceptions, and the ideas we have concerning the Other as well as about what constitutes our own best interest and our particular morality. The controls on our perceptions and self-understanding lie in a kind of treasure chest which we inherit or, to use a current idiom of the micro-chip generation, they lie in a floppy disk which lies in the eye of our mind. Whatever it is that we inherit, it comes not so much with our genes as with our cultural legacy, which is transmitted primarily through the process of our socialization. While such perceptions may be decisive in shaping our attitudes towards the situations we encounter, they are not necessarily permanent, for acquired attitudes which have been learned can also be unlearned, although this is often a more complicated process. In the realm of attitudes to the Muslim world, I feel that Americans are encumbered with a heavy legacy which lies at the root of the many enthusiasms and complacencies which have time and again been reflected in American foreign policy and in American reactions to events in that region ...